National Jail Census, 1988 ([Verlag nicht ermittelbar], 1990)
NATIONAL JAIL CENSUS, 1988, is the fifth in a series of data collection efforts aimed at studying the nation's locally administered jails. For purposes of this data collection, a jail was defined as a confinement facility intended for holding adults (and in some cases juveniles) pending adjudication or having sentences of a year or less. Jails were further defined as being administered and staffed by municipal or county employees. Also included in this collection were six jails privately operated under contract for local governments. Excluded from the census were federal or state-administered facilities, including the combined jail-prison systems in Alaska, Connecticut, Delaware, Hawaii, Rhode Island, and Vermont. The mailing list used for the census was derived from data gathered from the AMERICAN CORRECTIONAL ASSOCIATION DIRECTORY OF JUSTICE AGENCIES, publications such as AMERICAN JAILS, telephone calls to large metropolitan jail systems (e.g., New York City), state jail inspection bureaus, and newspaper articles. Following the initial mailout to 3,448 facilities, 44 jails were added and 176 deleted according to the criteria for inclusion, leaving a total of 3,316 facilities in 44 states. Variables include information on jail population by legal status, age and sex of prisoners, maximum sentence, admissions and releases, available services, structure and capacity, expenditure, and employment.